Perfil hematológico de serpentes Crotalus durissus linnaeus, 1758 (viperidae) e parasitismo por Hepatozoon (apicomplexa, hepatozoidae) no Estado de Minas Gerais. - Rafael Otavio Cancado Motta (2005)
This study aimed to establish the hematologic profile of Crotalus durissus the state of Minas Gerais and contribute to a better understanding of hemoparasitoses acomentem that these snakes. We analyzed 83 blood samples obtained from specimens of C. captured very hard in the state of Minas Gerais distributed among 30 females and 30 males newly captured 12 females and 11 males in captivity. Blood samples were used for diagnosis of Hepatozoon sp., calculate the percentage of parasitemia and policromotófilos (immature erythrocytes). From plasma samples obtained from the values of total plasmatic protein. The results of new animals captured were parasitized and not parasitized and compared with values obtained from captive animals. We established reference intervals for hematological C. durissus the state of Minas Gerais. Reported a prevalence of 38.3% of Hepatozoon sp. in the newly captured snakes. No positive animals were found among animals of cativeuiro. Snakes parasitized by Hepatozoon sp. demonstrate statistically significant increase in the percentage of polycrhomatophiles. Snakes free of Hepatozoon superior to animals infected, suggesting a negative influence of Hepatozoon sp. longevity of C. durissus